Antibacterial and anti-hyperlipidemic activities of the green alga Cladophora koeiei - Neveen Abdel-Raouf; Nouf Mohammed Al-Enazi; Ibraheem Borie Mohammad Ibraheem; Reem Mohammed Alharbi; Manal Mohammed Alkhulaifi (Beni-Suef University Journal of Basic and Applied Sciences, 2018)
In the present investigation, an antihyperlipidemic activity of Cladophora koeiei ethanol extract against six pathogenic bacteria was conducted. Also, we evaluate the activity of the alga extract against hyperlipedemia in the administrated albino rates through measuring the blood lipid profiles [triglycerides (TG), total cholesterol (TC), low-density lipoprotein (LDL-C), high-density lipoprotein cholesterol (HDL-C), cholesterol] and induced hepatic damage by measuring the contents of creatinine, total proteins, blood urea nitrogen (BUN), albumin and globulin and diagnostic marker enzymes such as aspartate aminotransaminase (AST) and alanine aminotransaminase (ALT). Alga extract proved efficient activity against the tested bacteria ranged between medium and high suppression action. Results revealed also, the efficiency of C. koeiei extract in the decreasing the triglycerides (TG), total cholesterol (TC), low-density lipoproteins (LDL-C), blood urea nitrogen (BUN) and creatinine caused by alcohol. However, the treatment by alga extract exhibits high-density of lipoproteins (HDL-C) (beneficial), total protein, albumin, and globulins. Also, the algal treatments masking the lethal effects caused by harmful alcohol from raising the rate of enzymes ALT, AST, which returned to the normal state in the groups treated with alga extract. Our findings provide the evidence that new natural antioxidant substances can be present in the C. koeiei extract and hence this alga proves to be effective as a source for therapeutic agents.